PENERAPAN PERHITUNGAN AKUNTANSI PRODUK UTAMA DAN PERLAKUAN AKUNTANSI PRODUK SAMPINGAN - Retnosari, Retnosari (JIAK : Jurnal Ilmiah Akuntansi dan Keuangan, 2016)
The purpose of this study was to determine the allocation of joint costs on the main products and by-products and to determine the accounting treatment of the main products and by-products of profit / loss in the UD Ngudi Rizeqy rice mill.From the calculation of profit and loss with three methods, namely reducing the cost of goods sold, reducing production costs and adding other income, profit margins are obtained. In the calculation by reducing the cost of goods sold and adding other income, the profit was Rp.31,316,470 in August, Rp.38,164,090 in September and Rp.38,041,020 for October. Whereas with the method of reducing production costs obtained a profit of Rp.31,108,350 in August, Rp. 37,891,250 in September and Rp. 37,816,110 in October. Treatment with a method of reducing production costs results in a smaller net profit due to lower production costs which results in a decrease in the value of the ending inventory and is followed by an increase in cost of goods sold.